2001
DOI: 10.1136/jms.8.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomised controlled trial comparing the effectiveness and cost-effectiveness of two primary care interventions aimed at improving attendance for breast screening

Abstract: Objectives-To examine the eVectiveness and cost-eVectiveness of two interventions based in primary care aimed at increasing uptake of breast screening. Setting-24 General practices with low uptake in the second round of screening (below 60%) in north west London and the West Midlands, UK. Participants were all women registered with these practices and eligible for screening in the third round. Methods-Pragmatic factorial cluster randomised controlled trial, with practices randomised to a systematic interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 14 publications
0
87
0
Order By: Relevance
“…Despite a diVerence in attendance rates of nearly 3% (11.2% v 8.3%; table 3) and an adjusted OR (95% CI) of 1.4 (0.9 to 2.1) the flag was not as clearly eVective as the letter. Also, the interaction between the flag and screening history found in the parallel trial 15 was not found here; hence that observation may well have been a chance finding. Flags have not previously been subjected to rigorous evaluation among non-attenders, 13 14 and therefore positive findings based on descriptive accounts 12 should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Despite a diVerence in attendance rates of nearly 3% (11.2% v 8.3%; table 3) and an adjusted OR (95% CI) of 1.4 (0.9 to 2.1) the flag was not as clearly eVective as the letter. Also, the interaction between the flag and screening history found in the parallel trial 15 was not found here; hence that observation may well have been a chance finding. Flags have not previously been subjected to rigorous evaluation among non-attenders, 13 14 and therefore positive findings based on descriptive accounts 12 should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 52%
“…For both interventions and particularly the flag, the extra costs to the health service per additional attendance were higher among recent non-attenders than for women before their routine invitation. 15 This is perhaps not surprising as non-attenders might be expected to be less amenable to interventions in primary care (at least in terms of absolute diVerences). This proposition is supported by the statistics about consultations and screening history (table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies such as colocation of preventive services, 10 patient letters, reminder phone calls and educational materials have been shown in studies of women without HIV to improve screening uptake, and they warrant evaluation in women with HIV. 26,29,30 Reminder letters for breast cancer screening are sent to patients in Ontario, and it is unclear why there is differential uptake among women with and without HIV. Physiciandirected interventions may be required, as physicians may emphasize the provision of HIV-specific primary care services to the detriment of routine, non-HIV-specific health screening, such as mammography.…”
Section: Resultsmentioning
confidence: 99%